IMPLEMENTASI SISTER CITY PEMERINTAH KOTA MEDAN -ICHIKAWA JEPANG DALAM MEWUJUDKAN PENDIDIKAN BERMUTU TAHUN 2018-2019 - Fezrin Inggrit Debora Nainggolan; Roberto Octavianus Cornelis; Sri Suwartiningsih (Yayasan Literasi Sains Indonesia, 2022)
Cooperation is an important thing in the era of globalization. Actors in carrying out cooperation no longer only include the state, but the local government is also able to carry out cooperation. Sister City is a long-term collaboration between two city governments in two countries. Medan City is one of the metropolitan cities in Indonesia which has several sister city activities, one of which is with the Ichikawa Government. The sister city collaboration between the Medan City Government and Ichikawa City Government has been established since the signing of the Memorandum of Understanding between the two cities on November 4, 1989. This study aims to see the implementation of cooperation between Medan-Ichikawa in realizing quality education using the Sister City approach and the theory of Institutional Liberalism. The research was conducted using qualitative methods, with data collection techniques in the form of interviews and library research.